2020
DOI: 10.1039/c9py01825e
|View full text |Cite
|
Sign up to set email alerts
|

Amplified photo-responses in sequentially polymerized azobenzene-containing polymer networks: the role of isomer interconnection

Abstract: Sequentially polymerized azobenzene-containing polymer networks with isomer-interconnected features can greatly enhance photo-actuation responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Light-induced long-lived deformation could be recovered on-demand through heating . Cho et al reported a one-pot synthesis method based on two-step sequential thiol–ene reactions for preparing azo-LCEs . In the first step, block-length-controlled azobenzene prepolymers (azo-prepolymers) were prepared in situ in a molten reaction mixture using the nucleophile-catalyzed chemoselective thiol-Michael reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Light-induced long-lived deformation could be recovered on-demand through heating . Cho et al reported a one-pot synthesis method based on two-step sequential thiol–ene reactions for preparing azo-LCEs . In the first step, block-length-controlled azobenzene prepolymers (azo-prepolymers) were prepared in situ in a molten reaction mixture using the nucleophile-catalyzed chemoselective thiol-Michael reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to thermosalient effects, the related jumping crystals are often referred to as the photosalient crystals. [37,91] The photoresponsive crystals in many cases occur with photochemical reactions, such as dimerization, [92][93][94][95] polymerization, [96,97] isomerization, [98] and ring closing and opening (Table 2). [99] Some of them are based on photoresponsive molecules or coordination complexes containing photoresponsive moieties, such as azobenzene, [100] diarylethene, [101,102] Schiff base, [103] and anthracene.…”
Section: Photomechanical Energy Conversionmentioning
confidence: 99%